Ultra-high-frequency ECG assessment of QRS fragmentation predicts sudden cardiac death risk in inherited arrhythmia syndromes. (3rd October 2022) - Saleh, K; Varnava, A; Shun-Shin, M J; Ali, N; Mohal, J; Chiew, K; Hanif, M A; Merzah, A J; Howard, J P; Jurak, P; Leinveber, P; Kanagaratnam, P; et al.
Abstract: Background: Fragmentation of the QRS complex, as a surrogate for scar or functionally disrupted ventricular activation, has been postulated as a risk factor for malignant ventricular arrhythmias across a range of cardiac diagnoses including cardiomyopathies, channelopathies and myocardial infarction. Fragmentation is subtle on the conventionally filtered 12-lead ECG and can easily be missed or over-diagnosed. Isolation of high-frequency (HF) QRS components could overcome this to demonstrate easily identifiable fragmentation but this has previously been limited by technological constraints resulting in a limited range of measured frequencies (150–300Hz). Ultra-high-frequency ECG (UHF-ECG) is a novel technology that utilises amplification and signal-averaging techniques to reliably measure frequencies up to 1000Hz. Purpose: We explored the use of UHF-ECG in arrhythmia risk stratification. Methods: We recruited 60 participants to undergo UHF-ECG recordings, including 23 healthy volunteers and 37 patients with inherited arrhythmia syndromes: 25 hypertrophic cardiomyopathy (HCM), 5 Brugada syndrome, 4 arrhythmogenic cardiomyopathy, 3 idiopathic ventricular fibrillation, 2 long QT syndrome and 1 non-ischaemic dilated cardiomyopathy. The arrhythmia risk status of patients with inherited disease was classified, by two independent researchers, into high or low risk based on their history of cardiac arrest, sustained ventricular arrhythmia, appropriate therapy, syncope and programmed ventricular stimulation result. A third researcher adjudicated disagreement. Two further researchers, blinded to aforementioned risk status, independently assessed the UHF-ECG recordings of all participants. Results: 40 patients were classified as low risk, and 20 as high. Healthy volunteer UHF-ECGs showed uniform ventricular activation with single HF peaks in each lead. High-risk patients' UHF-ECGs showed multiple HF peaks, representing QRS fragmentation. The maximum number of HF peaks in any lead was used to measure severity of fragmentation. Example UHF-ECGs are shown in Figure 1. Fragmentation severity (number of peaks) correlated with arrhythmia risk status (chi-square statistic = 8.95, p-value = 0.03) across all participants (Figure 2) and when comparing high to low risk patients with inherited disease. UHF-ECG fragmentation could be observed even when the 12-lead ECG did not show any observable fragmentation. Among patients with inherited disease, patients with HCM showed the largest difference in UHF-ECG fragmentation between high and low risk. UHF-ECG fragmentation analysis showed excellent reproducibility with no difference in number of peaks identified between two independent assessors. Conclusion: We demonstrate proof-of-concept that a novel ultra-high-frequency tool for measuring a broad range of high frequency QRS components can be used for sudden death risk stratification in patients with inherited cardiac conditions. Funding Acknowledgement: Type of funding sources: None.